2012
DOI: 10.1098/rstb.2012.0101
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of syntax: beyond string sets

Abstract: The human capacity to acquire language is an outstanding scientific challenge to understand. Somehow our language capacities arise from the way the human brain processes, develops and learns in interaction with its environment. To set the stage, we begin with a summary of what is known about the neural organization of language and what our artificial grammar learning (AGL) studies have revealed. We then review the Chomsky hierarchy in the context of the theory of computation and formal learning theory. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 105 publications
2
37
0
1
Order By: Relevance
“…Our source reconstructions confirm these localizations and suggest that they are specific to the intermediate time window of the MMR. The left inferior frontal pars opercularis area (Broca's area) location is also coherent with our use of vowel sequences, because this region is involved in the representation of structured language sequences (55).…”
Section: Discussionsupporting
confidence: 62%
“…Our source reconstructions confirm these localizations and suggest that they are specific to the intermediate time window of the MMR. The left inferior frontal pars opercularis area (Broca's area) location is also coherent with our use of vowel sequences, because this region is involved in the representation of structured language sequences (55).…”
Section: Discussionsupporting
confidence: 62%
“…However, these studies, several of which were discussed in Section 5, use tasks involving only English words and sentences, not programs. The following studies are particularly interesting, because they revealed the same Brodmann areas as our study: In studies related to reading comprehension and language processing, participants had to understand text passages or decide whether sequences of letters can be produced with rules of a formal grammar [3,9,21,24,25,26,28,30,55,56,68,74]. Regarding working memory, participants had to identify and apply rules or memorize verbal/numerical material [1,47,58,69].…”
Section: Related Workmentioning
confidence: 53%
“…Several studies suggest that real-time combinatorial operations in the IFG incorporate the current state of processing and incoming information into a new state of processing [30,56]. Hence, the IFG was proposed to be involved in the unification of individual semantic features into an overall representation at the multi-word level [74].…”
Section: Brodmann Areas 21 44 and 47mentioning
confidence: 99%
“…This mask consisted of bilateral IFG (BA 44, 45, 47), insula, anterior cingulate, STG, MTG, angular gyri, inferior parietal lobule, and supramarginal gyri. The mask covered the typical left perisylvian language areas that are of theoretical interest and their right hemisphere homologues (Dronkers et al, 2004; Friederici, 2012; Hickok & Poeppel, 2004, 2007; Petersson & Hagoort, 2012; Tyler & Marslen-Wilson, 2008), while excluding regions not typically involved in language processing. For visualisation, the volumetric statistically thresholded activation maps were projected onto the PALS-B12 surface atlas in CARET version 5.6.…”
Section: Methodsmentioning
confidence: 99%